An investigation for possible parallels of the Roman imperial cult (Caesar-Nero) in the New Testament book of Hebrews - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Dissertation (MTh (New Testament Studies))--University of Pretoria, 2007.